Brief Report: Takayasu Arteritis and Ulcerative Colitis: High Rate of Co‐Occurrence and Genetic Overlap. Issue 8 (28th July 2015) - Terao, Chikashi; Matsumura, Takayoshi; Yoshifuji, Hajime; Kirino, Yohei; Maejima, Yasuhiro; Nakaoka, Yoshikazu; Takahashi, Meiko; Amiya, Eisuke; Tamura, Natsuko; Nakajima, Toshiki; Origuchi, Tomoki; Horita, Tetsuya; et al.
<x xml:space="preserve">Abstract</x> Objective Takayasu arteritis (TAK) is a systemic vasculitis affecting large arteries and large branches of the aorta. Ulcerative colitis (UC) is a prevalent autoimmune colitis. Since TAK and UC share HLA–B*52:01 and IL12B as genetic determinants, and since there are case reports of the co‐occurrence of these diseases, we hypothesized that UC is a common complication of TAK. We undertook this study to perform a large‐scale analysis of TAK, both to evaluate the prevalence of concurrent cases of TAK and UC and to identify and estimate susceptibility genes shared between the 2 diseases. Methods We analyzed a total of 470 consecutive patients with TAK from 14 institutions. We characterized patients with TAK and UC by analyzing clinical manifestations and genetic components. Genetic overlapping of TAK and UC was evaluated with the use of UC susceptibility single‐nucleotide polymorphisms by comparing risk directions and effect sizes between susceptibility to the 2 diseases. Results Thirty of 470 patients with TAK had UC (6.4% [95% confidence interval 4.3–9.0]). This percentage was strikingly higher than that expected from the prevalence of UC in Japan. Patients with TAK complicated with UC developed TAK at an earlier stage of life (P = 0.0070) and showed significant enrichment of HLA–B*52:01 compared to TAK patients without UC (P = 1.0 × 10−5) (odds ratio 12.14 [95% confidence interval 2.96–107.23]). The 110 non‐HLA markers of susceptibility to UC significantly displayed common risk directions with susceptibility to TAK (P = 0.0054) and showed significant departure of permutation P values from expected P values (P < 1.0 × 10−10). Conclusion UC is a major complication of TAK. These 2 diseases share a significant proportion of their genetic background, and HLA–B*52:01 may play a central role in their co‐occurrence.